Utilization Status of Silver Rasbora (Rasbora argyrotaenia) in Kampar Kiri River, Lipat Kain Village, Kampar Kiri Sub District, Kampar - Kurniawan, Ikhsan; Prianto, Eko; Adriman, Adriman (Jurnal Perikanan dan Kelautan, 2025)
This research aims to determine the utilization status of silver rasbora (Rasbora argyrotaenia) in the Kampar Kiri River, Lipat Kain Village. This research was conducted in March-May 2024 in Sungai Kampar Kiri, Lipat Kain Village, Kampar Kiri Sub District. This research was carried out using a survey method to obtain primary data from measurements of fish caught. Fish sampling is carried out once a month for 3 months by seeing them directly in the Kampar Kiri River with the help of fishermen. The fish samples caught are put into a cool box and preserved using ice cubes. Then, they are taken to the laboratory to measure their length and weight for analysis using Microsoft Excel, FISAT II, and LB-SPR. This research obtained an SPR value for monitored fish of 83% or 0.83. The SPR value of this monitoring fish is still above the standard SPR limit (30% / 0.3). So, the status of silver rasbora utilization in the Kampar Kiri River is included in the under-exploited category.